2020
DOI: 10.1136/bmjopen-2019-036625
|View full text |Cite
|
Sign up to set email alerts
|

Role of community health workers in improving cost efficiency in an active case finding tuberculosis programme: an operational research study from rural Bihar, India

Abstract: ObjectivesCost-efficient active case finding (ACF) approaches are needed for their large-scale adoption in national tuberculosis (TB) programmes. Our aim was to assess if community health workers’ (CHW) knowledge about families’ health status can improve the cost efficiency of the ACF programme without adversely affecting the delivery of other health services for which they are responsible.DesignQuasi-experimental design.InterventionsWe evaluated an ACF programme in the Samastipur district in Bihar, India, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Although CHW have been involved in TB community activities, their involvement in the TPT management was quite unique in the CONTACT study (37) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although CHW have been involved in TB community activities, their involvement in the TPT management was quite unique in the CONTACT study (37) (15).…”
Section: Discussionmentioning
confidence: 99%
“…The project staff interfaced with the corresponding officials in the national TB program regularly. The organizational details have been described previously [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is hoped that the involvement of these members will make it easier for TB suspects to be examined because they are considered to be closer and more acquainted with the community than health workers. [8] From its establishment until now, the implementation of the TB community activities is still waiting for instructions from the TB program holders. There is no management in the TB community group, and the participation of members is still lacking.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Its area is about 169,616.65 Ha, consisting of 24 sub-districts, 325 villages, and 33 Puskesmas. [8] The Puskesmas in the Probolinggo Regency has implemented The TB case discovery by the TB community in Puskesmas Wangkal, Kraksaan, Krejengan, Pajarakan, and Maron in the last four years from 2017 to 2020 showed that the achievement of TB case detection had not met the target set.…”
Section: The Profile Of the Tb Community In Probolinggo Regencymentioning
confidence: 99%
See 1 more Smart Citation